Policy of Information and Communication Technologies to Promote the Formation of Future Business Models (Kebijakan Teknologi Informasi dan Komunikasi Untuk Mendorong Pembentukan Model Bisnis Masa Depan) - Mr. Ahmad Budi Setiawan (Jurnal Pekommas, 2017)
ICT industry becomes a driver of change, many sectors that can change not only from the telecommunications sector. ICT developments are spurring the digital economy enables sectors that had previously been in the safe zone, being threatened because of the presence of substitute industry that has begun to emerge. Trend to date, some companies use Internet-based applications to support the marketing of their products. Not only on the promotional activities featuring products that are known by consumers, even some companies use Internet technology to support transactions, such as the sale of products to consumers. Innovation and competition to push toward creative destruction, there is a long lost services and value added is replaced by the presence of ICT innovation. The government must be present and ready to anticipate the changes that may occur due to the development of ICT, which grew rapidly at the policy level. The study is qualitative and done through the study of literature and focused discussions involving experts and stakeholders concerned. the results of this study are as advice on policy will be taken by the government to the ICT industry sector forward in the face of the rapid innovation of ICT.Industri TIK menjadi driver dari suatu perubahan. Banyak sektor yang dapat berubah dan tidak hanya pada sektor telekomunikasi. Perkembangan TIK yang memacu terjadinya ekonomi digital memungkinkan sektor-sektor yang sebelumnya sudah dalam zona aman, menjadi terancam karena kehadiran substitusi industri yang sudah mulai bermunculan. Tren terbarui, beberapa perusahaan menggunakan aplikasi berbasis internet untuk mendukung pemasaran produknya. Tidak hanya pada kegiatan promosi yang menampilkan produk supaya diketahui oleh para konsumennya, bahkan beberapa perusahaan menggunakan teknologi internet ini untuk mendukung kegiatan transaksi, misalnya penjualan produk kepada konsumennya. Inovasi dan kompetisi memungkinkan untuk mendorong ke arah creative destruction, ada layanan lama yang hilang dan nilai tambahnya tergantikan oleh kehadiran inovasi TIK. Pemerintah harus hadir dan siap mengantisipasi perubahan-perubahan yang mungkin terjadi karena perkembangan TIK yang semakin pesat pada tataran kebijakan. Kajian bersifat kualitatif dan dilakukan dengan melalui studi literatur dan diskusi terfokus yang melibatkan para pakar serta pemangku kebijakan terkait. Hasil kajian ini dapat dijadikan sebagai rekomendasi untuk kebijakan yang akan diambil oleh pemerintah dalam sektor industri TIK kedepan dalam menghadapi pesatnya inovasi TIK.